DARI PENDIDIKAN HINGGA AKSI NYATA: MENGAPA BELA NEGARA ITU PENTING DI ERA MODERN? - Gading Adhip Arafa, Syafa (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to examine the importance of state defense education in forming public awareness and participation, especially the younger generation, in maintaining the integrity of the Unitary State of the Republic of Indonesia (NKRI). Through literature studies, this research analyzes various approaches to national defense education that have been implemented and evaluates their effectiveness in forming nationalistic character and attitudes. The research results show that national defense education has a very crucial role in fostering a sense of love for the country, increasing awareness of obligations as citizens, and preparing the younger generation to face challenges in the global era.